Some Effects of Physician Licensing Requirements on Medical Manpower Flows in Canada - Brown, Malcolm (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
In this paper the author examines the implications of the licensing regulations of physicians in Canada.